New Microstrip Diplexer for Recent Wireless Applications - S. Mezaal, Yaqeen; A. Hashim, Seham; H.Al-fatlawi, Aqeel; A. Hussein, Hussein (International Journal of Engineering and Technology, 2018)
In this study, dual-channel diplexer using microstrip open loop coupled resonators has been designed and simulated; each channel has two operating band frequencies. This microstrip diplexer is designed for (1.424/1.732GHz) for first channel and (2.014/2.318GHz) for second channel. The simulated results for this device have insertion loss (1.8 and 1 dB) at load 1, and (1.5 and 3 dB) at load 2. Additionally, it has reasonable return loss magnitudes better than 10 dB and effective isolation between channels of35 dB. The proposed design has shown an uncomplicated topology, an effectual design method, small circuit size and narrowband frequency responses that are fitting for multi service wireless schemes.Â Â